Counselling for depression a person-centred and experiential approach to practice - Sanders, Pete 1951-; Hill, Andrew (SAGE, 2014)
The first book to take a humanistic - person-centred/experiential - approach to counselling to the most commonly presenting client issue, depression. A landmark text, covering everything from evidence-based practice to training, supervision and research, it establishes humanistic counselling as an evidence-based psychological intervention--Source other than the Library of Congress.